Hydrogen sulfide reduces cell adhesion and relevant inflammatory triggering by preventing ADAM17‐dependent TNF‐α activation1. Issue 7 (9th May 2013) - Perna, Alessandra F.; Sepe, Immacolata; Lanza, Diana; Capasso, Rosanna; Zappavigna, Silvia; Capasso, Giovambattista; Caraglia, Michele; Ingrosso, Diego
Abstract H2S is the third endogenous gaseous mediator, after nitric oxide and carbon monoxide, possessing pleiotropic effects, including cytoprotection and anti‐inflammatory action. We analyzed, in an in vitro model entailing monocyte adhesion to an endothelial monolayer, the changes induced by H2S on various potential targets, including cytokines, chemokines, and proteases, playing a crucial role in inflammation and cell adhesion. Results show that H2S prevents the increase in monocyte adhesion induced by tumor necrosis factor‐α (TNF‐α). Under these conditions, downregulation of monocyte chemoattractant protein‐1 (MCP‐1), chemokine C‐C motif receptor 2, and increase of cluster of differentiation 36 could be detected in monocytes. In endothelial cells, H2S treatment reduces the increase in MCP‐1, inter‐cellular adhesion molecule‐1, vascular cell adhesion molecule‐1, and of a disintegrin and metalloproteinase metallopeptidase domain 17 (ADAM17), both at the gene expression and protein levels. Cystathionine γ‐lyase and 3‐mercaptopyruvate sulfurtransferase, the major H2S forming enzymes, are downregulated in endothelial cells. In addition, H2S significantly reduces activation of ADAM17 by PMA in endothelial cells, with consequent reduction of both ADAM17‐dependent TNF‐α ectodomain shedding and MCP‐1 release. In conclusion, H2S is able to prevent endothelial activation by hampering endothelial activation, triggered by TNF‐α. The mechanism of this protective effect is mainly mediated by down‐modulation of ADAM17‐dependent TNF‐converting enzyme (TACE) activity with consequent inhibition of soluble TNF‐α shedding and its relevant MCP‐1 release in the medium. These results are discussed in the light of the potential protective role of H2S in pro‐inflammatory and pro‐atherogenic processes, such as chronic renal failure. J. Cell. Biochem. 114: 1536–1548, 2013. © 2013 Wiley Periodicals, Inc.